Biggish data: Friedrich Engels, material ecology, and Victorian data. Issue 3 (3rd July 2019) - Parham, John
ABSTRACT: Through Friedrich Engels' The Condition of the Working Class in England (1845), this article examines two prominent themes in environmental humanities – vital ecological materialism and 'big data'. Engels' vivid descriptions of factories, houses, and environment shared the central tenets of 'material ecology' – 'thing power' (Jane Bennett); 'intra-actions' of social and material agency (Karen Barad); 'trans-corporeality' (Stacy Alaimo) – and met Bennett's call to align vital and historical materialism. The main body of the paper connects his analysis both to current debates about integrating 'big data' into social science and the humanities and to comparable nineteenth-century developments in statistics and data visualisation. Engels articulated the working-class condition by blending four distinct modes of investigation: big data; qualitative survey research; literary thick description; and theory (the nascent critique of capitalist political economy). Such a mix remains rich with possibilities for sociology and humanities not only in communicating but in generating knowledge about complex ecologies.